Flexural fatigue failure of concrete reinforced with smooth and mixing hooked-end steel fibers. Issue 1 (1st January 2019) - Saoudi, Nacira; Bezzazi, Boudjema
Abstract: This paper presents an experimental study on flexural fatigue dynamic behavior of reinforced concrete. Steel fiber is used for the retrofitting and strengthening flexural members, by mixing short smooth steel fiber and hooked-end fiber. By using Vibrophore HFP 150, dynamic loading was scanned at a resonance frequency of 100 Hz. Our objective is to examine the behavior of a specimen of 7 × 7 × 28 by a three-point bending test under high-level stress until it fails. Important research has been conducted to investigate the static and fatigue behavior of reinforcement. It was strengthened initially using one fiber, then using other additives. However, this research is not adequate to examine the flexural fatigue behavior of specimens by mixing different shaped fibers at different percentages. A further improvement in composite concrete performance is observed by mixing two steel fibers under high-level stress. The results are in alignment with the fatigue life data using Weibull distribution.